Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Studi Pada E-Commerce Lazada di Kota Bandung - Ade Ramadhan; Siti Sarah (eCo-Buss, 2024)
Lazada is an online shopping platform that provides a wide range of products, including electronics, stationery, children's toys and baby equipment, as well as health supplies and travel products. This lesson wants to know the impact of product and service quality to Lazada e commerce customer satisfaction within city Bandung. This lesson applies a descriptive and verifiable approach in a quantitative method. Probability sampling is a sampling technique in wherein element or fellow the population have the commensurate replacement become selected as a sample. The population in this study consists of 16.000,000 Lazada application users with samples 100 answerers. Data analysis approach applied includes data quality checks, classical assumption tests, normality tests, and influence tests. As on hypothesis examine, the t-test and f-test are used support by SPSS application. Outcome reveal lest product quality had a significant influence with a tcal value of 5,008 and a significan level of 0.000. In addition, service quality also own significan clout on customer satisfaction, with a T count value of 2,306 and a significan level of 0.023. Simultaneously, these two factors contribute significantly to customer satisfaction, as evidenced by the f-value of 3,895 and p-value 0.19. That’s possible resume that there is a significant relation among product quality and e-service quality and customer satisfaction. on Lazada Bandung.